Evaluation of Impact of Biofertilizer and Mulch Types on Growth and Production of Tomato Cultivar Gustavi F1 in Lowland Areas - Kartina, Raida; Rahhutami, Ratih; Darma, Wika Anrya; Putri, Sekar Utami; Tiara, Dede; Taisa, Rianida; Fahri Ali, Fahri Ali (Universitas Sanata Dharma, 2024)
Tomato plants are expected to have an ideal growing environment to optimize their growth and production. Therefore, this study aimed to investigate the effect of various concentrations of biofertilizer, mulch types, and their interactions on growth and production of the Gustavi F1 tomato cultivar. A randomized group design (RGD) arranged factorially was used for the analysis, with the first factor consisting of no mulch (M0), straw mulch (M1), and plastic mulch (M2). The second factor was five biofertilizer concentrations, including 0 ml.l-1 (L0), 5 ml.l-1 (L1), 10 ml.l-1 (L2) 15 ml.l-1 (L3), and 20 ml.l-1 (L4). Data were analyzed using the F test (analysis of variance), and in cases of significant differences, the analysis proceeded with Duncan Multiple Range Test (DMRT) at an α level of 5%. Growth parameters observed in the experiments included plant height at 1 and 3 weeks after planting, while production parameters comprised fruit diameter, the number of fruits per plant, the percentage of fruits experiencing Blossom End-Rot (BER), and fruit weight per plot. The results showed that the use of plastic mulch significantly increased the number of fruits per plant, while the 0 ml.l-1 biofertilizer concentration showed the most effective reduction in the percentage of fruits experiencing BER. Moreover, an interaction between mulch and biofertilizer treatments was observed, particularly in relation to plant height 1 week after planting, the number of fruits per plant, and the percentage of fruits experiencing BER.Keywords— generative, microbes, ground cover, vegetative